2013
DOI: 10.1002/lary.23773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating internet health resources in ear, nose, and throat surgery

Abstract: The use of validated instruments is necessary to reduce the risks from patients accessing misinformation. They can guide health care professionals with their role in directing patients to high-quality sources of information and endorsing Web sites that meet high standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
4
31
1
Order By: Relevance
“…The majority of sites studied had at least "moderate" accessibility, usability, and reliability. This compares favorably to a previous study examining LIDA in other otolaryngologic disorders (Goslin and Elhassan 2013). This study also found that the vast majority of sites have moderate ratings for all three nonquality measures, with reliability having the widest range of scores-this reflects the homogenous nature of sites when it comes to user interface and interactivity, but heterogeneity when examining frequency of updates and sources of information.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The majority of sites studied had at least "moderate" accessibility, usability, and reliability. This compares favorably to a previous study examining LIDA in other otolaryngologic disorders (Goslin and Elhassan 2013). This study also found that the vast majority of sites have moderate ratings for all three nonquality measures, with reliability having the widest range of scores-this reflects the homogenous nature of sites when it comes to user interface and interactivity, but heterogeneity when examining frequency of updates and sources of information.…”
Section: Discussionsupporting
confidence: 75%
“…Quality was 'excellent' or 'good' for the majority of websites studied (29/33, 87.9%). The average DISCERN score of 56.6 is higher than any other topic examined within the otolaryngology literature, including OSA (Goslin and Elhassan 2013;Pusz and These encouraging results carried over to non-quality measures as well. The majority of sites studied had at least "moderate" accessibility, usability, and reliability.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Seven of the 14 sources failed to mention any associated risks of the options reported. Previous work assessing the online health information for other conditions has produced similar findings [34,35].…”
Section: Discussionsupporting
confidence: 55%
“…Although the quality of online information has been evaluated for a range of conditions [9,10] there have been no studies into the quality and content of websites on herbal remedies for menopausal symptoms. The objectives of this study were to assess the quality and coverage of website information; to compare commercial and non-commercial providers; and assess how well the information fits with what women want.…”
Section: Introductionmentioning
confidence: 99%